Impact of the Russia-Ukraine war on the energy sector in southeast asia - Ilman, Nauvan Zam; Anam, Muhammad Zahrul (Jurnal Inovasi Ilmu Sosial dan Politik (JISoP), 2023)
The conflict between Russia and Ukraine has spread, having a variety of implications on the global community. Where the world's two biggest energy producers are at conflict with one another. In this research, topics like "climate ambition," the impact of rising oil prices on each of Southeast Asia's nations, and its impact on airline ticket costs are discussed. The purpose of this research was to determine whether Southeast Asia's influence was tied to energy. Data for this study is gathered by content analysis of published books, websites, and journals. Qualitative methods of descriptive explanatory research are used to characterize the object or subject under study, while explanatory answers explain why a situation or circumstance exists. The findings of this study revealed several factors related to Southeast Asia's failed "climate ambition," as well as an increase in oil prices, which caused many Southeast Asian countries to experience price increases for basic goods. Meanwhile, some countries are spared significant consequences because they have their own oil resources Southeast Asian countries with their own sources of oil energy are less affected by the Russia-Ukraine war, but overall inflation of 4.7% at the end of 2022 hampered climate ambition. This research will use qualitative with normative method which find the fact thar Ukraine and Rusia war is impacted to economic global including Asia through global trade.